1985
DOI: 10.1007/bf00137646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected repeated intravitreal chemotherapeutic agents

Abstract: The toxic effects of repeated intravitreal injections of selected chemotherapeutic agents were studied in female albino rabbits. Three groups of eyes participated in each therapeutic regimen. Agents studied were doxorubicin (dox), 3 and 5 micrograms; 5-fluorouracil (5-FU), 0.375 and 1.0 mg; bleomycin (bleo), 15 micrograms; thiotepa (thio), 12 micrograms; etoposide (VP-16), 150 micrograms; and methotrexate (MTX), 600 mic. Toxicity was evaluated using electroretinography (ERG) in 66% and histopathology in 100% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…11,12 However, some antimetabolites have been shown to be safe. Methotrexate has been shown to be clinically nontoxic when injected into human eyes at doses of 400 µg.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, some antimetabolites have been shown to be safe. Methotrexate has been shown to be clinically nontoxic when injected into human eyes at doses of 400 µg.…”
Section: Discussionmentioning
confidence: 99%
“…The optic nerve and medullary rays also appeared intact in both the treated and control eyes [65] . Another study determined the retinal toxicity of combined chemotherapy in rabbit eyes, which consisted of: 5-FU, 375 g; doxorubicin, 3 g; neomycin, 15 g; thiotepa, 12 g; etoposide, 150 g, and MTX, 600 g. This combination regimen caused a severe ERG decrease (decrease in b-wave amplitude to less than 25%) and retinal changes (generalized thinning of the retina, disorganization of retinal layers and loss of photoreceptor outer segments) [71] .…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…As early as 1985, it has been shown that 600 g MTX combined with other chemotherapeutic agents such as doxorubicin, 5-FU and bleomycin enhanced the risk of retinal toxicity [71] . However, in one recent study, the ocular pharmacokinetics and retinal toxicity of intravitreal MTX sodium at 400 g were studied in New Zealand white rabbits.…”
Section: Enzymes and Fibrinolyticsmentioning
confidence: 99%
“…Some of the reported examples of MTX neurotoxicity are: acute transient cerebral dysfunction (32), death of nerve cells in the brain stem (33) and degeneration of the autonomic nerve fibers in the small intestine (34). Severe toxicity on retina resulted as evaluated by electroretinography (35). A survey of the literature reveals that many, if not all, anticancer drugs can inhibit different enzymes in vitro and in vivo (22-24, 36, 37).…”
mentioning
confidence: 99%